Exploring Effective Assessment in Students’ ESP Writing Skill: A Conceptual Framework - Ardhy, Andi Anugrah Surya (Journal of English Language Teaching, Linguistics, and Literature Studies, 2023)
This study explores effective assessment in improving students' English for SpecificPurposes (ESP) writing skill. Using the PRISMA systematic literature review researchmethod, this study highlights the important role of assessment in building meaningfullanguage skills in a specific field of study. The assessment of ESP writing skill goesbeyond the mechanical aspect, focusing on communicative dimensions such as clarity,cohesion and accuracy in a given context. An ongoing and targeted approach toassessment provides constructive feedback to students, enabling them to improve theirwriting skill strategically. The alignment between content and language skillsemphasizes the importance of accurate assessment in achieving learning objectives anddeveloping effective communication skills. Adopting innovative approaches, such asVirtual Learning Object Development (VLO), illustrates ESP education's potential fortechnological transformation. A paradigm shift towards appropriate assessmentmethods, such as authentic and dynamic approaches, promotes contextual learning andholistic development. Challenges in ESP assessment, including context-specific criteriaand student barriers, highlight the need for responsive and diverse teaching strategies.By addressing these challenges and adopting appropriate assessment techniques,educators can facilitate students' readiness to meet the communication demands oftheir field of study, creating success in both academic and professional contexts.Keywords: Assessment, Students’ ESP, Writing skill